1969
DOI: 10.1104/pp.44.12.1672
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide metabolism in plants: specificity of peroxidases for aniline substrates.

Abstract: Studies on the metabolism in plants (4,5,6, 8) aInd in soil (1, 2) of the herbicide propanil (3,4-dichloropropionanilide) have showin that the parent compound is rapidly hydrolyzed to release 3,4-dichloroaniline (DCA). In plants, the aniline moiety is recovered in several compounds including sugar and lign,in conjugates (6, i7) Fig. 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1975
1975
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Bartha and Bordeleau (1) developed a method to quantify peroxidase activity in soil by using a dimethoxylated aniline (o-dianisidine) as the substrate. Differences in the substrate specificities of peroxidases from different sources were reported by Lieb and Still (19). Peroxidases from barnyard grass (Echinoczhloa crusgalli) and rice plants showed greater substrate specificity on chlorinated anilines than horseradish peroxidase.…”
mentioning
confidence: 76%
“…Bartha and Bordeleau (1) developed a method to quantify peroxidase activity in soil by using a dimethoxylated aniline (o-dianisidine) as the substrate. Differences in the substrate specificities of peroxidases from different sources were reported by Lieb and Still (19). Peroxidases from barnyard grass (Echinoczhloa crusgalli) and rice plants showed greater substrate specificity on chlorinated anilines than horseradish peroxidase.…”
mentioning
confidence: 76%
“…Our analysis did not detect features consistent with the TDZ monomer in African violet tissues and our synthetic biotransformation analysis indicated that the TDZ molecule is cleaved at the amide bridge releasing a thidiazol ring and aniline. Aniline is the product of metabolism of several herbicides and is incorporated into sugar and lignin conjugates [ 49 ]. Previous researchers have determined that derivatives of the 1,2,3-thidiazol-5yl ring are potent anti-senescence compounds [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using previously described methods synthetic biotransformations were applied to the thidiazuron molecule in Excel: −H 2 , +H 2 , −CH 3 , +CH 3 , +C 6 H 12 O 6 , −C 6 H 12 O 6 , +OH, +OH (×2), +COOH, +NH 2 , +NH 3 , −H, +H [ 37 , 47 , 48 , 49 ]. The monoisotopic mass for each biotransformation (±0.02 Da) was mined within our dataset in order to identify potential anabolic or metabolic products.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…for horseradish peroxidase (Sigma type II), EC 1.11.1.7, by the procedure of Lieb and Still (1969). The reaction mixture was incubated for 10 min at 23 °C, and then extracted with 1 vol of chloroform.…”
Section: Methodsmentioning
confidence: 99%